RESPONSIBILITY TO PROTECT (RTPR) UNITED NATIONS ENVIRONMENT PROGRAMME (UNEP) DALAM PENANGANAN ANCAMAN KRISIS AIR DI OGONI NIGERIA TAHUN 2006-2011 - Mita Prayatni, I Dewa Ayu; Sushanti, Sukma; Intan Prameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT This research aims to analyze the UNEP process in response facing the threat of water crisis in Ogoni, Nigeria through Responsibility To Protect (RTPR) in human security perspective. The water crisis caused a threat to the survival of the Ogoni community by decreasing the water quantity supply, increasing economic, social and health issues. This issue discussed by answering question to how UNEP implementing the Responsibility to Protect (RTPR) in dealing with water crisis issues in Ogoni, Nigeria. This research used collected data from various sources including, literary sources, news and reports. Data were analyzed with responsibility to protect of international community from human security perspective in international relations. By using descriptive qualitative method,this research shows what is done by UNEP as a fulfillment of the fundamental rights of the Ogoni community through environmental assessment project and regulatory policy recommendations as well as build a facility sanitation and water supply. Keywords:Nigeria, Water Crisis, UNEP, Human Security, Responsibility to protect (RTPR